Understanding the Effect of Aluminum Addition on the Forming of Second Phase Particles on Grain Growth of Micro-Alloyed Steel - Abro, S. H.; Moria, H. A.; Chandio, A.; Al-Khazaal, A. Z. (Engineering, Technology & Applied Science Research, 2020)
The formation of second phase particles in the steel matrix during melting and casting plays an important role in controlling the grain size of steel. An attempt is made in the present work to find the role of nitrogen on forming nitride particles either with aluminum or titanium. Two steel samples with the same titanium and aluminum weight percent in their chemical composition were collected after the hot rolling process. Solution heat treatment at 1350°C for 60min holding time was used to dissolve the particles and then the steel samples were reheated at 800°C for 60min, water quenched and their microstructure was revealed by usual grinding and polishing process using 2% Nital. A transmission electron microscope connected with EDS was used to reveal the morphology of the second phase particles. The samples for TEM analysis were prepared by the replica extraction method in 5% Nital solution. The samples were then caught in 3mm copper grid for TEM analysis. TEM micrographs revealed the second phase particles in the matrix of steel. EDS peaks were studied and titanium peaks were found in both samples and surprisingly there was not any peak found for aluminum.